Analisis Failure Mode And Effect Analysis Proyek X Di Kota Madiun - Aan Zainal Muttaqin; Yudha Adi Kusuma (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2018)
Failure Mode and Effect Analysis (FMEA) is a structured procedure to identify and prevent as many failure modes as possible. A failure mode is anything that is included in the defect, conditions outside the specified specifications, or changes in the product that cause disruption of the function of the product. The methodology used is descriptive research where data collection is obtained from library research and field research in the form of interviews and direct observation. In the data analysis conducted there were 46 Potential failures of the project activities. Then do the calculations on the value of the impact caused, then the value on the failure caused and the value on prevention. Of the three values are multiplied to calculate the priority value. The highest RPN is obtained on 9 indicators, namely planning, work contracts, Workshops and post-project activities, unexpected events, political conditions, costs, quality and time. The three highest indicators are planning with RPN 179.65, then RPN employment contract of 137.09 and Workshop activities with RPN 170.85. The total RPN of the 9 indicators is 1289.37 and the critical value is 143.26Failure Mode and Effect Analysis (FMEA) adalah suatu prosedur terstruktur untuk mengidentifikasi dan mencegah sebanyak mungkin mode kegagalan. Suatu mode kegagalan adalah apa saja yang termasuk dalam kecacatan, kondisi diluar spesifikasi yang ditetapkan, atau perubahan dalam produk yang menyebabkan terganggunya fungsi dari produk (Gasperz, 2002). Metodologi yang digunakan adalah penelitian deskriptif dimana pengumpulan data didapatkan dari penelitian kepustakaan dan penelitian lapangan yang berupa wawancara dan pengamatan langsung. Hasil yang didapat berupa 3 indikator risiko kritis tertinggi di proyek X yaitu perencanaan, kegiatan di workshop dan kegiatan pasca proyek dengan nilai 179,65; 170,85 dan 157,25.